THE INFLUENCE OF THE FORTA INTERVENTION ON DRUG THERAPY IN HOSPITALIZED ELDERLY PATIENTS - Wehling, M. (Innov Aging, 2017)
The absence of data regarding the efficacy and safety of many drugs for use in the elderly has been a major issue. The FORTA categorization (A: Absolutely; B: Beneficial; C: Careful; D: Don’t) was proposed as an aid for improving the appropriateness of pharmacotherapy in the elderly. To evaluate the usefulness of FORTA we conducted a prospective randomized trial (n=409). We determined the alterations in medication and over- and under-prescription rates between admission and discharge. Both over- and under-treatment were improved in the FORTA group as compared to the control group (p<0.0001). In this study, we are going to identify the drugs which were the major determinants for the observed alterations and analyze the overall use of therapeutic groups in our cohort. Based on our results, FORTA is the first combined positive/negative labelling approach at the individual drug level which indeed ameliorates the drug treatment of the elderly.